Math, asked by arjunprasada33517, 10 months ago

 In an expression ax² + bx + c the sum and product of the factors respectively …….. ​

Answers

Answered by SRodriguez9970
4

Answer:

MARK AS BRAINLIEST

by using Quadratic formula;

x =   \frac{ - b +  -  \sqrt{ {b}^{2} - 4ac }  }{2a}  \\  \\ sum \: of \: factors \: is. \\  \\  \frac{ - b +    \sqrt{ {b}^{2} - 4ac }  }{2a}  +  \frac{ - b  -  \sqrt{ {b}^{2} - 4ac }  }{2a}  \\  \\  =   \frac{ - 2b}{2a}  \\  \\  =  \frac{ - b}{a}

product \: of \: factors \: is. \\  \\ \frac{ - b +    \sqrt{ {b}^{2} - 4ac }  }{2a} \times  \frac{ - b    -  \sqrt{ {b}^{2} - 4ac }  }{2a}  \\  \\  =   \frac{  {( - b)}^{2} -  ({ \sqrt{ {b}^{2}  - 4ac} })^{2}  }{4 {a}^{2} }  \\  \\  =   \frac{ {b}^{2} -  {b}^{2}  + 4ac }{4 {a}^{2} }  \\  \\  =  \frac{c}{a}

Similar questions